What are you afraid of: Collective leadership and its learning implications - and Raelin, Joseph A (Management Learning)
In this provocation, the author attempts to cite the advantages of collective leadership while acknowledging the objections and fears of challengers. Collective leadership is seen as remote because it defies the traditional view of leadership as an individualistic attractive quality that not only protects us but is efficient when applied. Nevertheless, the collective alternative may not only be advisable but required in a connected world featuring a networked economy. The contemporary socio-politico-economic environment requires the contribution of, creativity from, and collaboration among multiple agents providing a dynamic concentration of management and knowledge. If we are to accept and recognize the contribution of a collective leadership, its development would require an entirely different learning model. In particular, collective leadership development occurs as an acute immersion into the practices that are embedded within in situ material–discursive relations—in other words, among people, objects, and their institutions.